Characterization of a Pathogenic Variant in the ABCD1 Gene Through Protein Molecular Modeling. (25th January 2020) - Richter Jr., John E.; Vadlamudi, Charitha; Macklin, Sarah K.; Samreen, Ayesha; Helmi, Haytham; Broderick, Daniel; Mohammad, Ahmed N.; Hines, Stephanie L.; VanGerpen, Jay A.; Atwal, Paldeep S.; Caulfield, Thomas R.
Abstract : Background. The ATP-binding cassette, subfamily D, member 1 (ABCD1) protein is a peroxisomal half-transporter that allows for very long chain fatty acid (VLCFA) degradation. Pathogenic variants of ABCD1 cause VLCFAs to build up in various tissues and bodily fluids, resulting in a disorder called X-linked adrenoleukodystrophy (X-ALD). This disorder is most commonly marked by adrenocortical insufficiency and high VLCFA concentration, and has varying levels of neurological involvement depending on phenotype. For example, the Addison-only form of X-ALD has no neurological impact, while the cerebral form of X-ALD often causes severe sensory loss, motor function impairment, cognitive decline, and death. Methods. A newly characterized and suspected pathogenic variant in ABCD1 was analyzed using our protein informatics platform (PIP). Personalized protein-level molecular studies were completed on genetic testing data, complementing the analysis and clinical study. Results. A case of adult onset adrenomyeloneuropathy (AMN) and a novel ABCD1 variant are presented. The unique ABCD1 protein is discussed, and the proband's case is compared to existing reports of AMN. Conclusions. Data fusion from multiple sources was combined in a comprehensive approach yielding an enriched assessment of the patient's disease and prognosis. Molecular modeling was performed on the variant to better characterize its clinical significance and confirm pathogenicity.